Answer:
6 students
Step-by-step explanation:
x = the number of students in front of peter
y = the number of students behind peter
z = the number of students who left, for 3 < z < 9 ∴ z ∈ {4, 8}
system of equations:
- 2(x-z) = y (assuming that the students who left were all among the students who are in front of peter)
x = 2y ⇒ y = x/2 (defining y with x)
2(x-z) = y (lets substitute y)
2(x-z) = x/2
2x-2z = x/2
2(2x-2z) = x
4x-4z = x
4x-x = 4z
3x = 4z
if z = 6 (i pluged the numbers from 4 to 8)
then
3x = 4×6
3x = 24
x = 24/3
x = 8
∴ y = 4
8 students were in front of peter and 4 were behind him
6 left
now 2 students are in front of peter and 4 are behind him
8 is twice 4
8-6 = 2
4 is twice 2